1991
DOI: 10.1104/pp.97.4.1494
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine Ammonia-Lyase from Tomato Cell Cultures Inoculated with Verticillium albo-atrum

Abstract: Tomato (Lycopersicon esculentum Mill.) cell suspension cultures accumulated wall-bound phenolic materials in response to inoculation with VerticiliIum albo-atrum Reinke et Berth. in a fashion analogous to that observed in whole plants. Both monomeric and polymeric materials were recovered. Deposition of phenolics into the cell walls of inoculated tomato cell cultures was inhibited by the phenylalanine ammonia-lyase (PAL) inhibitor, 2-amino-2-indanephosphate. Tomato PAL activity was induced over 12-fold by fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In this respect, it is known that PAL is the key enzyme in phenolic-compound biosynthesis, and it has been reported that it is activated and its expression induced in response to different stress conditions, among these, an increase in light (Hemm et al 2004;Jaakola et al 2004) and nitrate deficiency (Fritz et al 2006). Different studies mention that PAL-activity increases during the first days of stress, and once the required compounds have been synthesized, the enzyme's activity decreases (Bernards and Ellis 1991;Kováčik and Bačkor 2007). When C. peltata plants were submitted to different treatments, PAL activity could have increased to a maximum in days prior to the analysis, with which phenolics were synthesized and later diminished to levels observed at the end of the treatments (d28).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In this respect, it is known that PAL is the key enzyme in phenolic-compound biosynthesis, and it has been reported that it is activated and its expression induced in response to different stress conditions, among these, an increase in light (Hemm et al 2004;Jaakola et al 2004) and nitrate deficiency (Fritz et al 2006). Different studies mention that PAL-activity increases during the first days of stress, and once the required compounds have been synthesized, the enzyme's activity decreases (Bernards and Ellis 1991;Kováčik and Bačkor 2007). When C. peltata plants were submitted to different treatments, PAL activity could have increased to a maximum in days prior to the analysis, with which phenolics were synthesized and later diminished to levels observed at the end of the treatments (d28).…”
Section: Discussionmentioning
confidence: 95%
“…Under conditions of high photosynthesis rate or reduction of available nitrogen (N), production of C-based defense compounds will be favored, whereas under the opposite conditions, N-based defense compound synthesis will be carried out (Coviella et al 2002;Fritz et al 2006;Grechi et al 2007). According to these predictions, it has been demonstrated that the production of phenolics can be stimulated by low nitrate levels (Armstrong et al 1970;Fritz et al 2006;Palumbo et al 2007;Le Bot et al 2009), high light (Hemm et al 2004;Jaakola et al 2004;Mosaleeyanon et al 2005) and other biotic and abiotic stresses, e.g., pathogen attack, mechanic wounding, ultraviolet (UV) radiation, low temperatures and nutrient deficit (Bernards and Ellis 1991;Kováčik and Bačkor 2007;Clé et al 2008;Jansen et al 2008). Phenylalanine ammonia-lyase enzyme (PAL) catalyzes the conversion of phenylalanine into trans-cinnamic acid; therefore, this enzyme causes the flux of primary into secondary metabolites in the phenolics pathway.…”
Section: Introductionmentioning
confidence: 94%
“…Other studies on the phenylalanine ammonia lyase enzyme in tomato, although limited, are consistent with the current analyses. Fungal inoculations of tomato cell cultures have been reported not to result in multiple forms of the enzyme (32).…”
Section: Discussionmentioning
confidence: 99%
“…It plays a major role in the catabolism of L-phenylalanine. In higher plants, PAL has been extensively studied because of its role in plant development and its response to a wide variety of environmental stimuli (Bernards & Ellis, 1991;Havir & Hanson, 1973;Jones, 1984;Rosler et al, 1997;Santiago et al, 2009). In microorganisms, PAL was demonstrated for the first time by Ogata et al (1966).…”
Section: Introductionmentioning
confidence: 99%